2018
DOI: 10.12973/iji.2018.11438a
|View full text |Cite
|
Sign up to set email alerts
|

Linking Homework to Achievement in Mathematics: An Examination of 8th Grade Arab Participation in TIMSS 2015

Abstract: Homework is generally one factor that has been discussed and claimed to have a relationship with achievement; it has a central role in providing students with opportunities to continue learning out of the school. This study forms one of crosscultural investigations that analyze the links between homework variables and achievement in mathematics. Data was drawn from TIMSS database 2015, including 477 schools and 73,987 eighth grade students from 10 Arab countries. Analysis showed that the majority of Arab stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Most of the teachers aimed to assign homework in order to increase the academic development of the students, such as their understanding of the subject and ensuring knowledge retention. Similar to the results of the present study, Abdelfattah and Lam (2018), Brock et al (2007) and Rosairo et al (2015) determined that mathematics homework increased academic success. On the other hand, Kapıkıran and Kıran (1999) and, Güven and Akçay (2019) found that homework assignments for primary school students in mathematics class did not affect their academic success.…”
Section: Purpose Of the Homeworksupporting
confidence: 90%
See 1 more Smart Citation
“…Most of the teachers aimed to assign homework in order to increase the academic development of the students, such as their understanding of the subject and ensuring knowledge retention. Similar to the results of the present study, Abdelfattah and Lam (2018), Brock et al (2007) and Rosairo et al (2015) determined that mathematics homework increased academic success. On the other hand, Kapıkıran and Kıran (1999) and, Güven and Akçay (2019) found that homework assignments for primary school students in mathematics class did not affect their academic success.…”
Section: Purpose Of the Homeworksupporting
confidence: 90%
“…They stated that these assignments were generally in the form of exercises. Many studies reported that teachers used homework assignments for reinforcement and repetition purposes (Abdelfattah & Lam, 2018;Büyükalan & Altınay, 2018;Ersoy & Anagün, 2009;İflazoğlu & Hizmetçi, 2006;Medwell & Wray, 2018;Ok & Çalışkan, 2019;Taş et al, 2014). Rosairo et al (2015) stated that reinforcement type assignments increased the achievement levels in primary school mathematics class.…”
Section: Purpose Of the Homeworkmentioning
confidence: 99%
“…The strength of the relationship between homework and pupil achievement in mathematics is not yet fully clear; the results of studies are inconsistent. Some researchers found a positive relationship (e.g., Cheema & Sheridan, 2015;Abdelfattah & Lam, 2018), some studies generated contradicting findings (Cooper, Robinson & Patall, 2006;Dettmers, Trautwein & Lüdtke, 2009). Dettmers, Trautwein and Lüdtke (2009) showed in their study rooted in PISA 2003 a significant positive relationship between the students' scores in mathematics and the time spent doing homework at the group level.…”
Section: Discussionmentioning
confidence: 95%
“…PISA 2012 showed that pupils in Poland and Estonia spend about twice more time with homework than pupils in the Czech Republic and Slovenia (OECD, 2014c). Abdelfattah and Lam (2018), based on the results of TIMSS in 15 Arab countries, determined that longer homework (taking more than 60 minutes) is annoying for the pupils, while shorter and less frequent homework (1 to 4 times a week) reflects an important way to improve their achievement. According to Maňák (1992), pupils must be sufficiently motivated to do homework.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, with regards to the total digital devices at home, findings indicate that students with more digital devices at home (β= 8.67, p-value < 0.001) tend to outperform students with no digital devices. This could be because students with more digital devices have access to more resources such as the internet to assist them with mathematics related tasks (Abdelfattah & Lam, 2018).…”
Section: The Relationship Between Using Information and …mentioning
confidence: 99%